Molecular diagnosis of Pseudomonas aeruginosa isolated from clinical and milk samples - HANAA DAAJ KHALAF AL-MOZAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Al-Mozan HDK. 2024. Molecular diagnosis of Pseudomonas aeruginosa isolated from clinical and milk samples. Biodiversitas 25: 2648-2655. The extensive use of antiseptic and disinfectants, which are not free of quaternary ammonium compounds, which has occurred recently, led to the emergence of drug-resistant bacteria. The current study aimed to determine the accurate method of identification, the presence of QacE, and QacE?1 genes in Pseudomonas aeruginosa isolated from milk compared to P. aeruginosa of clinical isolates, and the relationship between the presence of QacE, QacE?1 genes, and multidrug resistance. Therefore, 27 clinical and 34 milk samples were collected and examined by biochemical and molecular methods to detect P. aeruginosa bacteria. Also, a susceptibility test was performed. The results exhibited that 13 (21.3%) isolates were identified as P. aeruginosa using biochemical methods, 8 (13.1%) isolates were identified as P. aeruginosa by molecular method; the QacE and QacE?1 genes were 100% and 83.3% for clinical isolates and 50% and 100%, respectively, for milk isolates. Both isolates showed superior resistance to ceftazidime and vancomycin, but the clinical isolates outperformed the milk isolates by 50% to ciprofloxacin, and imipenem. Clinical isolates were resistant to a greater number of drugs compared to milk isolates. The isolates with the accession numbers (LC805650, LC805652, and LC805651) were registered as new strains. Expression of QacE, QacE?1 genes should be examined to know the true relationship.